A thick SiC-Si coating prepared by one-step pack cementation for long-term protection of carbon/carbon composites against oxidation at 1773 K. (15th May 2022) - Zhang, Bei; Yi, Maozhong; Ning, Yao; Xie, Aolin; Zhou, Zhe; Feng, Zhirong
Abstract: A thick SiC-Si coating for carbon/carbon (C/C) composites is prepared by one-step pack cementation (PC) process. The microstructure of the coating, the interface structure between the coating and the substrate, and anti-oxidation properties are investigated. As-prepared coating with a thickness of about 774 µm has a dense and microcrack-free structure. Oxidation test results showed that weight gain of SiC-Si coated specimens is about 8.1 mg·cm −2 after oxidation at 1773 K for 338 h, and no failure. By exploring the oxidation resistance of coatings with different thicknesses, it can be found that thickness has a positive effect on coating performance. Highlights: A thick and dense SiC-Si coating is prepared by pre-oxidation and one-step PC. The inner face of the coating is obtained and investigated. The coating can protect C/C composites 338 h at 1773 K in air and remains intact. Coating thickness has positive effect on the SiC-Si coating.